The influence of national culture on remote work - Taboroši Srđana; Maljugić Biljana (Trendovi u Poslovanju)
With globalization and the emergence of a growing number of international companies, the influence of national culture on various aspects of human life in management has become particularly important in recent decades in modern business. Due to the encounter of different cultures from all over the world, it is impossible to avoid the influence of these cultural differences and the possibility of conflicts is great, so modern leaders and managers try to find good techniques of proper management of different people using knowledge of national culture. Any form of conflict, even constructive conflicts, can have a negative impact on the work performance of employees, and in international companies a large number of conflicts is a direct consequence of a lack of understanding of national culture. Teleworking and flexible forms of work are the result of the technological revolution and globalization. Although insufficiently researched form of work, it is gaining more and more attention of the authors. Managers face new challenges in managing employees working remotely, especially in multinational and multiethnic environments of international companies, so it is important to explore aspects that affect their work performance.